A Brief Analysis on Labor Supply Exercises in the Human Resources Information Framework - Joynob Akter Nishu (Garuda Prestasi Nusantara Consulting, 2022)
The association has used the Human Resources Information Framework (HRIF) with the development of innovation. HRIF is expected to increase the feasibility of training in providing human resources (human resource development) in associations. In this paper, we talk to two HRIF heads in the accommodation business to differentiate between the benefits, efforts, and difficulties of HRIF. HRIF distinguishes jobless positions, accurately investigates each position in the association and its position, understands the competent authority's preparation needs, selects the ideal talent to prepare at the right time, and prepares the program. . Faster and more precise choice regarding replacement placement. Thus, HRIF is thought to play an essential role in managing human resources. Associations need to integrate HRIF with other trusted frameworks to take advantage of good information sharing and independent direction.